2020
DOI: 10.1108/jsbed-06-2020-0219
|View full text |Cite
|
Sign up to set email alerts
|

A model for digital development of SMEs: an interaction-based approach

Abstract: PurposeE-business maturity models have been widely used to guide the process of digital transformation of business. However, these models have been criticized for their predominantly technocentric approach, which is poorly suited for SMEs. The purpose of this paper is to produce a holistic, nonlinear e-business development model for SMEs that takes into account the interactions of the organization in the pursuit of its business objectives.Design/methodology/approachBased on the literature review, this paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…In the Portuguese context, the two regions with most economic capacity in the country, Lisbon and Porto, stand out. It is there where there exist a greater number of more developed firms, confirming the relationship between the maturity of the websites and the organization's performance [36].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In the Portuguese context, the two regions with most economic capacity in the country, Lisbon and Porto, stand out. It is there where there exist a greater number of more developed firms, confirming the relationship between the maturity of the websites and the organization's performance [36].…”
Section: Discussionmentioning
confidence: 62%
“…This study is framed in the field of models to measure the maturity of websites. In the general field of assessing the effectiveness of a website, the authors consider the quality of the website to be an important area for research, where what is valued is not the characteristics of the website but its functionalities [36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal context of SMEs is being transformed (Lee 2016 ; Neirotti et al 2019 ). Rosenblat and Stark ( 2016 ) have shown that digital technologies positively influence the employee-employer relationship in terms of autonomy and control, as they bring greater flexibility (Depaoli et al 2020 ). Digital technologies have a direct impact on the work of entrepreneurs and managers, which in turn affects SMEs performance and competitiveness (Corvello et al 2021 ; Secundo et al 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The app has allowed Bistrot to expand its customer base by reaching tourists and local people alike. Tourists check Bristrot's reviews on websites like Trip Advisor, resulting in new business opportunities [35].…”
Section: 4 Promotion Of Entrepreneurship In Europe: Italy Urban Contextmentioning
confidence: 99%